Development of technology for producing enhanced fuel from low-grade coals (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article discusses an innovative method for obtaining refined solid fuel using a pyrolysis plant and the development of a technology for processing low-grade coals from the southern region of Kyrgyzstan. The purpose of the research is to develop a technology for obtaining refined fuel from low-grade coals in Kyrgyzstan and their effective use in the heat and power industry and the construction industry of the country.The novelty of the proposed idea is the use of a pyrolysis plant to obtain refined solid fuel and the development of a technology for processing low-grade coals; as a result of experimental studies, high-quality import-substitutable fuel was obtained - semi-coke.
Keywords: coal, thermochemical process, pyrolysis plant, refined fuel, innovative approach, semi-coke